An Energy Efficient Protocol Increasing Wireless Sensor Networks Lifetime Using Clustering Technique - Prasad, Sanjana; Sunder, A. John Clement (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Wireless Sensor Networks (WSNs) have been predicted to be in all domains in the near future. However in order to reach this scenario, researchers are finding a solution to some difficulties which are slowing down the wide spread use of these networks. One the activity done by WSN that consumed the most energy is the number of packets sent/received. In order to reduce this and to ensure WSN successful operation, hierarchical clustering protocols have been developed. -TEEN and WBM-TEEN: two hierarchical routing protocols, based on nodes clustering and improving the well-known protocol Threshold sensitive Energy Efficient sensor Network protocol (TEEN) are presented . This improvement is accomplished in a way such that each cluster is node balanced and the total energy consumption between sensor nodes and cluster heads is minimized by using multi-hops intra-cluster communication. Simulation results (using NS2 simulator) show that the proposed protocols exhibit better performance than Low Energy Adaptive Clustering Hierarchy (LEACH) and TEEN in terms of energy consumption and network lifetime prolongation